2015
DOI: 10.1001/jamasurg.2015.25
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Quality of Life and Risk Factors for Recurrence After Laparoscopic Repair of Paraesophageal Hernia

Abstract: Overall, laparoscopic repair of PEH with biological mesh results in excellent long-term QOL. The cause of recurrence is likely multifactorial and individualized to each patient. Further evaluation of novel techniques and unidentified patient factors is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 34 publications
(31 reference statements)
0
38
0
7
Order By: Relevance
“…With these data, it is possible to think that an asymptomatic small gastric reherniation is frequently observed after operation, without this being considered a true recurrence. This idea is also shared by Lidor et al 21 The lengths of gastric folds observed above the esophagogastric junction should be separated into 3 categories: smaller than 2 cm, 3 to 5 cm, and larger than 5 cm. The following categorization of recurrence is proposed, assigning a score to the presence of symptoms, endoscopic findings and radiologic findings: no recurrence, 0 points; asymptomatic recurrence, 1 point (relative recurrence); and symptomatic recurrence, 2 to 3 points (''true'' or absolute recurrence).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…With these data, it is possible to think that an asymptomatic small gastric reherniation is frequently observed after operation, without this being considered a true recurrence. This idea is also shared by Lidor et al 21 The lengths of gastric folds observed above the esophagogastric junction should be separated into 3 categories: smaller than 2 cm, 3 to 5 cm, and larger than 5 cm. The following categorization of recurrence is proposed, assigning a score to the presence of symptoms, endoscopic findings and radiologic findings: no recurrence, 0 points; asymptomatic recurrence, 1 point (relative recurrence); and symptomatic recurrence, 2 to 3 points (''true'' or absolute recurrence).…”
Section: Discussionmentioning
confidence: 77%
“…A total of 29 patients (23%) had recurrence, and only 9 (31%) were symptomatic, and the quality of life was significantly better after surgery. Lidor et al 21 showed there was a significant improvement in symptoms score in all patients, even in patients with recurrent hiatal hernia. Also, the quality-of-life index improved similarly.…”
Section: Discussionmentioning
confidence: 92%
“…This is similar with previously published recurrence rates using this common definition. Lidor et al in their series of Type III hernias noted a one-year recurrence rate of 27% with this definition (13). In the largest review of laparoscopic GPEH repair, Luketich et al examined their decade of experience, and noted a recurrence rate of 15.7% at a median of 22 months after repair.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have examined the results of GPEH repair in a prospective manner with routine imaging post-operatively. The prospective data with routine post-operative barium swallow studies that do exist is hindered by small study populations or low patient participation at long-term follow-up (12, 13). Therefore, the objective of this trial was to prospectively evaluate all patients undergoing elective repair of GPEH, and to evaluate these patients for recurrence and measures of quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…However most patients remain asymptomatic, thus the relevance of this method may be questioned. 82,83 Median time for radiologic recurrence is 40 months. 84 It might be beneficial to only report symptomatic recurrence, which is more relevant in the treatment of patients.…”
Section: Predictors For Outcomementioning
confidence: 99%